Habitat use by two extremophile, highly endemic, and critically endangered fish species (Gambusia eurystoma and Poecilia sulphuraria; Poeciliidae). Issue 6 (7th April 2016) - Culumber, Zachary W.; Hopper, Garrett W.; Barts, Nicholas; Passow, Courtney N.; Morgan, Samuel; Brown, Anthony; Arias‐Rodriguez, Lenin; Tobler, Michael
Abstract: Effective conservation measures for endangered species require basic knowledge of habitat use and critical environmental variables influencing the species' occurrence. However, setting priorities may be difficult when multiple endangered species inhabit the same area and differ in habitat use. This study characterized the physical and chemical environment at 30 sites along a 2.5 km stretch of stream associated with the Baños del Azufre hydrogen sulphide spring complex, home to the only population of the widemouth gambusia ( Gambusia eurystoma ) in existence. Also present in the spring is Poecilia sulphuraria, a narrowly endemic and endangered species known from only a few populations. This study provides the most detailed report to date for physical and chemical drivers of species density in this small, extreme environment. Gambusia eurystoma were generally rare throughout the stream, and stream flow and substrate size were the best predictors of G. eurystoma densities. Conversely, P. sulphuraria were considerably more abundant, but no physical or chemical variables predicted their density among sites. Size distributions of adult P. sulphuraria were significantly influenced by stream flow and water chemistry, indicating a cost to living in greater proximity to toxic springs with high hydrogen sulphide concentrations. Overall, the results provide the first extensive report of environmental variation and factors associated with G. eurystoma densities, and indicate that conservation measures prioritizing environmental conditions for G. eurystoma will also benefit P. sulphuraria . Fish in sulphide springs provide prime examples of narrowly endemic species in desperate need of conservation, and their habitats face conservation challenges similar to those found in other springs with sympatric, endemic species in the world's arid regions. Copyright © 2016 John Wiley & Sons, Ltd.